PENGARUH KUALITAS PELAYANAN, KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PERUSAHAAN DISTRIBUSI BAHAN KIMIA - Rugeri Fadhli Halim (Jurnal VOK@SINDO, 2020)
The purpose of this study was to analyze several influences between service quality, customer satisfaction that creates customer loyalty in a chemical distribution company in Malang. The research method used is explanatory research with a quantitative approach. The population in this study are consumers who have and have made purchase transactions at the company. The sample used is a representativeness sample, and with a Roscoe scale so that a total population of 100 respondents is found. The results showed that service quality did not have a significant effect on customer satisfaction, because not all good company service quality will give satisfaction to customers. On the other hand, customer satisfaction has a significant effect on loyalty, customer loyalty will be obtained if the company can increase customer satisfaction, especially in company management.